Hospitality law : managing legal issues in the hospitality industry - Barth, Stephen (Hoboken, New Jersey : Wiley, 2012)
"Written to help teach hospitality students what they need to know to manage a facility legally, safely, and securely"
Contents: Ch. 1 Prevention philosophy -- Ch. 2 Government agencies that impact the hospitality industry -- Ch. 3 Hospitality business structures -- Ch. 4 Contract basics -- Ch. 5 Significant hospitality contracts -- Ch. 6 Legally managing property -- Ch. 7 Legally selecting employees -- Ch. 8 Legally managing employees -- Ch. 9 Your responsibilities as a hospitality operator -- Ch. 10 Your responsibilities as a hospitality operator to guests -- Ch. 11 Your responsibilities for guests' property -- Ch. 12 Your responsibilities when serving food and beverages -- Ch. 13 Legal responsibilities in travel and tourism -- Ch. 14 Safety and security issues -- Ch. 15 Managing insurance.
Includes index.
Keywords: HOTELS -- LAW AND LEGISLATION -- UNITED STATES